2020
DOI: 10.1126/sciadv.aba6584
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of two-pore channels in antigen-presenting cells promotes the expansion of TNFR2-expressing CD4 + Foxp3 + regulatory T cells

Abstract: CD4+Foxp3+ regulatory T cells (Tregs) are pivotal for the inhibition of autoimmune inflammatory responses. One way to therapeutically harness the immunosuppressive actions of Tregs is to stimulate the proliferative expansion of TNFR2-expressing CD4+Foxp3+ Tregs via transmembrane TNF (tmTNF). Here, we report that two-pore channel (TPC) inhibitors markedly enhance tmTNF expression on antigen-presenting cells. Furthermore, injection of TPC inhibitors including tetrandrine, or TPC-specific siRNAs in mice, increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
(46 reference statements)
0
14
0
Order By: Relevance
“…Tetrandrine is a known blocker of the two-pore channel, and this property of tetrandrine can inhibit the host cell entrance of ebola virus, MERS-CoV, and SARS-CoV-2 spike protein pseudovirions [142][143][144]. Recently, we reported that inhibition of the two-pore channel in APC by tetrandrine enhanced the expression of mTNF on APC and consequently induced the proliferative expansion of Tregs via TNFR2 signaling [145,146]. Further, we also found that tetrandrine potently inhibited the differentiation of Th1, Th2 and Th17 cells, while sparing the differentiation of Treg cells [139].…”
Section: Tetrandrinementioning
confidence: 99%
“…Tetrandrine is a known blocker of the two-pore channel, and this property of tetrandrine can inhibit the host cell entrance of ebola virus, MERS-CoV, and SARS-CoV-2 spike protein pseudovirions [142][143][144]. Recently, we reported that inhibition of the two-pore channel in APC by tetrandrine enhanced the expression of mTNF on APC and consequently induced the proliferative expansion of Tregs via TNFR2 signaling [145,146]. Further, we also found that tetrandrine potently inhibited the differentiation of Th1, Th2 and Th17 cells, while sparing the differentiation of Treg cells [139].…”
Section: Tetrandrinementioning
confidence: 99%
“…Previously, we showed that TET inhibited colitis through Tregs in TNFR2 dependent manner ( 13 ). To assess if this amelioration from psoriasis-like skin inflammation after TET NE treatment ( Figure 4 ) was attributed to TNFR2 expression, WT, or TNFR1 -/- or TNFR2 -/- mice were treated with IMQ daily for 6 days.…”
Section: Resultsmentioning
confidence: 96%
“…Thus, boosting the Tregs function in psoriasis patients has the potential to alleviate psoriasis. Strikingly, our previous work has demonstrated that TET, a traditional Chinese medicine-derived small compound could promote Tregs expansion by enhancing tmTNF expression on antigen-presenting cells through tmTNF/TNFR2 signaling in vivo ( 13 ). Simultaneously, TET did not promote or inhibit the in vitro generation of iTregs ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the mice colitis model, we showed that the expanded Tregs are attributable to the reduced colon inflammation after tetrandrine treatment. [49][50][51] Furthermore, TNFR2 is closely associated with the immunosuppressive function of Treg cells, and the expression of TNFR2 can define the highly suppressive subset of Tregs. 22,25,46,52 Moreover, the number of Tregs in TNFR2 −/− mice is markedly lower than in wild-type (WT) mice, and when stimulated with the septic challenge, they fail to expand.…”
Section: Dovepressmentioning
confidence: 99%